2008
DOI: 10.1152/ajpregu.00105.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food availability and leptin on the physiology and hypothalamic gene expression of the golden spiny mouse: a desert rodent that does not hoard food

Abstract: Food availability and quality in desert habitats are spatially and temporally unpredictable, and animals face periods of food shortage. The golden spiny mouse (Acomys russatus) is an omnivorous desert rodent that does not hoard food, requiring it to withstand such periods by physiological means alone. In response to food restriction, plasma leptin concentrations, core body temperature, and energy expenditure of the spiny mouse decrease significantly after 24 h, and most spiny mice are able to maintain their bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…; Gutman et al . , , ). They do not hoard food, have no cheek pouches and consume mainly animal matter, which is difficult to store; therefore, food foraged is food consumed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Gutman et al . , , ). They do not hoard food, have no cheek pouches and consume mainly animal matter, which is difficult to store; therefore, food foraged is food consumed.…”
Section: Introductionmentioning
confidence: 99%
“…Golden spiny mice defend their body mass by using torpor during food shortage periods and gain fat mass when food is plentiful (Kronfeld-Schor et al 2000;Ehrhardt et al 2005;Gutman et al 2006Gutman et al , 2007Gutman et al , 2008. They do not hoard food, have no cheek pouches and consume mainly animal matter, which is difficult to store; therefore, food foraged is food consumed.…”
Section: Introductionmentioning
confidence: 99%
“…There is a report on the appetite regulation in response to food restriction in a desert rodent, the golden spiny mouse, Acomys russatus [31]. Acomys do not store food, unlike Notomys, and thus respond quickly to food restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased leptin expression has often been associated with neuroendocrine and neurochemical changes in response to fasting or FD (Ahima et al 1996;Doring et al 1998). For example, food restriction resulted in upregulation of AgRP and NPY in the arcuate nucleus of the hypothalamus associated with decreased leptin expression in striped hamsters , golden spiny mice (Gutman et al 2008) and rats [Rattus norvegicus (Berkenhout, 1769)] (Brady et al 1990;Schwartz et al 1993;de Rijke et al 2005;Johansson et al 2008;Sucajtys-Szulc et al 2008). In the present study, the hypothalamic AgRP showed a marginal increase (P = 0.06) in FD males compared to the control males, which is consistent with previous findings (Wen et al 2018).…”
Section: Morphological Changesmentioning
confidence: 99%
“…For example, the level of serum leptin (a hormone that is mainly produced by adipocytes and has been implicated in energy expenditure and balance) has been shown to decrease in food-deprived animals (Mercer et al 1998;Schneider et al 2000;Mustonen et al 2008;Speakman & Mitchell 2011;Gao et al 2014) and such decreased serum leptin was associated with decreased fat mass as a result of fasting (Ahima et al 2000). FD also increased hypothalamic gene expression of neuropeptides such as neuropeptide Y (NPY) and agouti-related protein (AgRP) in the golden spiny mouse [Acomys russatus (Wagner, 1840)] (Gutman et al 2008). Interest-ingly, leptin supplement attenuated food restriction-enhanced gene expression of NPY and AgRP in the hypothalamus of striped hamster, indicating that leptin may play a key role in mediating responses to fasting Wen et al 2018).…”
Section: Introductionmentioning
confidence: 99%